THE TRANSLATION OF COLLOCATIONS IN AUTHENTIC HADITH FROM ARABIC INTO ENGLISH - KHALEL, AHMAD RAMADHAN (Journal of Duhok University, 2019)
Translating collocation is not an easy task as collocations play a vital role in languages. The present study tries to investigate problems that translators of religious texts encounter while translating collocations from Arabic into English in The Authentic Hadith. The same Hadiths are taken from Saheh Al-Bukharyas corpus, depending on two translations by two professional translators namely Muhammad Muhsin Khan-translator of Saheh Al-Bukhary(1997),Nasiruddin al-Khattab-translator of Saheh Moslem(2007) .The findings of the study showed that translators have used different strategies in order to overcome the  problems of translating collocations in religious texts . The main objective of this study is To examine the difficulties encountered by the three translators in translating collocations in religious texts, consequently they tend to use several inadequate translation strategies as soon as translation cannot be carried out adequately.The study tried to answer the following questions:What are the problems that the translators may face when translating collocation from Arabic into English in Authentic Hadith? What are the strategies that the translators use while translating collocations in religious texts?